ผลของความเครียดเกลือต่อการงอกและการเติบโตในระยะต้นกล้าของข้าว: Effects of Salt Stress on the Germination and Early Seedling Growth of Rice - Saengsanga, Thanakorn; Aukaew, Chalotorn; Rodsanthia, Krissada (Asian Health, Science and Technology Reports, 2017)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลของความเครียดเกลือต่อการงอกและการเติบโตในระยะต้นกล้าของข้าว ศึกษาการตอบสนองต่อความเค็ม 6 ระดับ (0, 4, 8, 12, 16 และ 20 dS m-1) ในข้าว 8 สายพันธุ์ ผลการทดลอง พบว่าความเค็มมีผลทำให้เปอร์เซ็นต์การงอก ความเร็วการงอกและพลังงานการงอกลดลง และส่งผลให้ความยาวและน้ำหนักแห้งรากและยอดลดลงอย่างมากเมื่อความเค็มเพิ่มมากขึ้น ข้าวทุกสายพันธุ์ยกเว้นเหลืองประทิวสามารถทนทานต่อความเครียดเกลือได้ดีโดยสามารถงอกได้มากกว่า 85% ที่ความเค็ม 16 dS m-1 และที่ 20 dS m-1 ข้าวขาวดอกมะลิ 105 สามารถงอกได้แต่ข้าวเหลืองทองและเหลืองประทิวถูกยับยั้งอย่างสมบูรณ์ แต่เมื่อวิเคราะห์น้ำหนักแห้งที่ลดลง ข้าวพันธุ์เหลืองปลาซิวทนทานต่อความเครียดเกลือโดยมีเปอร์เซ็นต์น้ำหนักแห้งลดลงน้อยที่สุด จากเปอร์เซ็นต์น้ำหนักแห้งที่ลดลงข้าวพันธุ์เหลืองปลาซิวถูกจัดเป็นสายพันธุ์ทนเค็ม (T) ที่ 12 dS m-1 ส่วนขาวดอกมะลิ 105 เหลืองทอง ขาวตาแห้ง ลอยเกษตร หอมโคราช และเหลืองประทิวเป็นสายพันธุ์ทนเค็มที่ 4 dS m-1 และสะกอเป็นสายพันธุ์ทนเค็มปานกลาง (MT) The objective of this study was to determine the effects of salt stress on the germination and early seedling growth of rice. The response of eight rice varieties against six salinity levels (0, 4, 8, 12, 16 and 20 dS m-1) were studied. The results showed that salinity significantly decreasing final germination percentage, speed of germination, germination energy and led to decreasing in shoot and root length and dry weight in all varieties when increased salinity level. All verities except Leuang Pratew exhibited greater salt tolerance which was >85% germination at 16 dS m-1 salinity. At 20 dS m-1 salt concentration, germination was found in Khao Dawk Mali 105 but completely arrested in Leuang Tong and Leuang Pratew. Based on dry matter reduction, Leuang Prasew showed greater degree of salt tolerance than those of rice and it was classified as tolerant (T) plant at 12 dS m-1 salinity level. In case, Khao Dawk Mali 105, Leuang Tong, Khao Ta Heang, Loy Kaset, Hom Korat and Leuang Pratew were categorized to be tolerant and Sa Khor was also classified as moderately tolerant plant at 4 dS m-1.